2010
DOI: 10.1590/s1415-47572010000100021
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis and genotype-by-environment interaction of grain protein content in durum wheat

Abstract: Parental, F1 , F 2 , BC 1 and BC 2 generations of four crosses involving four cultivars of durum wheat (Triticum durum Desf.) were evaluated at two sites in Tunisia. A three-parameter model was found inadequate for all cases except crosses Chili x Cocorit 71 at site Sidi Thabet and Inrat 69 x Karim at both sites. In most cases a digenic epistatic model was sufficient to explain variation in generation means. Dominance effects (h) and additive x additive epistasis (i) (when significant) were more important than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
7
10
0
1
Order By: Relevance
“…The traits SL, SG and TKW showed low heritability values, indicating little additive variation and also that the genetic effects of dominance and epistatic interactions had a significant influence, adding to an important component of environmental variation. These results are in accordance with reports published by other authors in wheat (Bnejdi and El Gazzah 2010;Erkul et al 2010;Dvojković et al 2010;Sultan et al 2011;Abd El-Rahman 2013;Amin 2013). The negative dominance variance for SP, SS, HW and GY may be due to micro-environmental variations, sampling errors and / or the fact that the basic generations are inefficient to determine the variance of dominance in the analysis (Novoselović et al 2004;Dvojković et al 2010).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The traits SL, SG and TKW showed low heritability values, indicating little additive variation and also that the genetic effects of dominance and epistatic interactions had a significant influence, adding to an important component of environmental variation. These results are in accordance with reports published by other authors in wheat (Bnejdi and El Gazzah 2010;Erkul et al 2010;Dvojković et al 2010;Sultan et al 2011;Abd El-Rahman 2013;Amin 2013). The negative dominance variance for SP, SS, HW and GY may be due to micro-environmental variations, sampling errors and / or the fact that the basic generations are inefficient to determine the variance of dominance in the analysis (Novoselović et al 2004;Dvojković et al 2010).…”
Section: Resultssupporting
confidence: 93%
“…The low effects of additive and the duplicate epistasis determine that selection in the early segregating generation is not efficient. The presence of significant epistatic effects for these traits were reported by several authors in wheat (Bnejdi and El Gazzah 2010;Tonk et al 2011;Ali et al 2014;Hassan and El-Said 2014;Darwish and El-Nahas 2015). However, many publications indicated that the results depend on the parents used and the evaluation site or environment.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Thus, the possibility to enhance GPC through plant breeding may be limited, although not completely absent (e.g. Bnejdi & El Gazzah, 2010;Bogard et al, 2010). The conclusion of Kibite & Evans (1979) is generally consistent with the pattern obtained in the present study, where close relationships between effects on GPY and GY, especially for O 3 , were found over a wide range of genetic variation represented by a large number of cultivars.…”
Section: Discussionsupporting
confidence: 89%